Cover. (24th September 2018) - Bourlev, Vladimir; Moberg, Christian; Ilyasova, Natalia; Davey, Eva; Kunovac Kallak, Theodora; Olovsson, Matts
Abstract : The cover image, by Vladimir Bourlev et al., is based on the Original Article Vasoactive intestinal peptide is upregulated in women with endometriosis and chronic pelvic pain, DOI:10.1111/aji.12857 .